Role of metabolic syndrome and lifestyle factors in endometrial cancer risk and prevention - Anita Kwiatkowska; Natalia Małek; Sara Emerla; Aleksandra Brożyna; Arkadiusz Bydliński; Konrad Karłowicz; Maria Hermanowska; Julia Lubomirska; Patrycja Figurowska; Łukasz Ciulkiewicz (Quality in Sport)
Introduction: The incidence of endometrial cancer, the sixth most common cancer among women, has been rising, especially in developed countries, possibly due to the obesity and diabetes pandemic. The aim of this review is to investigate the connection between metabolic syndrome, its individual components and endometrial cancer risk and to explore the role of lifestyle factors in endometrial cancer prevention.